Association of serum levels and intakes of sodium and potassium with hypertension in the MASHAD cohort study population: a cross-sectional study - Alireza Sherkati; Sara Saffar Soflaei; Susan Darroudi; AmirAli Moodi Ghalibaf; Sina Esmaeili; Niloufar Abdollahian; Sahar Arabpour; Mahyaar Omouri-Kharashtomi; Mohammad Mirzaei; Behzad Ensan; Maryam Allahyari; MohammadReza Latifi; et al. (Journal of Health, Population and Nutrition)
Abstract Background and aim Hypertension is a major health problem and a risk factor for multiple diseases. In this study, we aimed to compare serum levels and the dietary intake of sodium and potassium in patients with hypertension and healthy participants of the MASHAD cohort study. Methods and design All participants of the MASHAD cohort study entered the study. Systolic blood pressure (SBP) ≥ 140 mmHg or diastolic blood pressure (DBP) ≥ 90 mmHg or a history of hypertension were defined as hypertension. Demographic variables were collected by health care professionals. Sodium and potassium dietary intake were measured using a food frequency questionnaire. Serum levels of sodium and potassium were measured using routine methods by electrolyte analyzer. Data were analyzed using SPSS version 18. Binary logistic regression model was used control for confounding factors. The significance level was set at p < 0.05. Results Of the total 9,704 participants of the Mashhad study, 6,641 participants had normal blood pressure and 3063 were hypertensive individuals. No significant difference in serum levels of sodium and potassium was observed between the two groups (p = 0.700, p = 0.360 respectively). After adjusting for confounding factors, the association remained the same. Sodium and potassium dietary intake was significantly higher in the hypertensive group and after adjusting for baseline characteristics, an increase in dietary sodium intake is associated with a higher likelihood of hypertension by 0.8% (CI, 1.000-1.015). Conclusion Serum sodium and potassium levels were not associated with hypertension among MASHAD participants. Increased dietary intake of sodium was associated with hypertension even after adjusting for confounding factors.